Effects of Tartary buckwheat on physicochemical properties and microbial community of low salt natural fermented soybean paste. (August 2022) - Xiao, Longquan; Lapu, Molazi; Kang, Shuai; Jiang, Peng; Li, Jing; Liu, Yang; Liu, Dayu; Liu, Mingxue
Abstract: It is a valuable attempt to use Tartary buckwheat as the raw material of soybean paste due to its functional composition. In this research, the soybean pastes were prepared with Tartary buckwheat flour and wheat flour by low salt natural fermentation (10%, w/v NaCl), respectively; the physicochemical properties and microbial community structure of samples prepared from the two groups were investigated. The results showed that Tartary buckwheat promoted the accumulation of protease, total acid (TA), amino acid nitrogen (AAN) significantly compared with the control group during fermentation ( p  < 0.05). Both groups had similar bacterial communities, Klebsiella, unidentified _Chloroplast, Bacillus, Staphylococcus, Enterococcus, Acinetobacter, Weissella were present in all samples. But the fungal communities of the two groups were significantly different. The dominant fungi in all samples were Rhizopus and Aspergillus . In moromi fermentation, the Issatchenkia presented only in buckwheat group, Stenocarpella and Gibberella were characteristic fungi of wheat flour group. The changes of biodiversity and community structure showed that the microbial communities of the two groups experienced different succession patterns. The results can provide a reference for the further development of low salt Tartary buckwheat soybean paste and the study of microbial community succession in soybean paste fermentation. Highlights: Effects of Tartary buckwheat flour on soybean paste were investigated. Soybean pastes were naturally fermented with low salt concentration (10%, w/v). Physicochemical properties of soybean paste are mainly affected by microbial succession. In moromi fermentation, Issatchenkia presented only in buckwheat group. Stenocarpella and Gibberella were characteristic fungi of wheat flour group.